2003
DOI: 10.1590/s0100-06832003000500001
|View full text |Cite
|
Sign up to set email alerts
|

Compressibilidade de um Latossolo Vermelho argiloso de acordo com a tensão de água no solo, uso e manejo

Abstract: RESUMOUma das principais conseqüências do manejo inadequado do solo é a sua compactação, que leva à perda da sustentabilidade agrícola. O objetivo deste trabalho foi o de estudar o comportamento compressivo de um Latossolo Vermelho argiloso, sob quatro tensões de água no solo, sob cerrado, sob plantio direto e cultivo convencional, utilizando-se o arado de discos, após duas décadas de uso. Amostras não deformadas foram utilizadas na caracterização da porosidade do solo e nos ensaios de compressão uniaxial. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
15

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
(33 reference statements)
1
8
0
15
Order By: Relevance
“…It can be argued that, for the study area is under no tillage for several years, where traffic systematic machinery, associated with inadequate water content of soil, may be contributing to compaction and increased resistance to penetration. OLIVEIRA et al (2003), studying tension and compressibility of water in a Clayey Oxisol, concluded that the pressures on land can decrease the porosity, hindering the development of plants. SILVA et al (2006) found that the water content of the soil has great influence on the deformation and compression of it.…”
Section: Resultsmentioning
confidence: 99%
“…It can be argued that, for the study area is under no tillage for several years, where traffic systematic machinery, associated with inadequate water content of soil, may be contributing to compaction and increased resistance to penetration. OLIVEIRA et al (2003), studying tension and compressibility of water in a Clayey Oxisol, concluded that the pressures on land can decrease the porosity, hindering the development of plants. SILVA et al (2006) found that the water content of the soil has great influence on the deformation and compression of it.…”
Section: Resultsmentioning
confidence: 99%
“…Nos dois sistemas de cultivo, a densidade do solo aumentou da superfície até 0,15 m, sendo maior na camada de 0,05 a 0,15 m e a partir dessa diminuiu (Figura 1). Em relação à mata, o aumento da densidade foi observado até 0,35 m, sendo de 71 % no PR e 86 % no PC, na camada de 0,05 a 0,10 m, e 16 % no PR e 10 % no PC, de 0,30 a 0,40 m. Essa compactação, em comparação à condição original, foi devida às pressões exercidas sobre o solo pelo trânsito de máquinas e implementos agrícolas, durante 25 anos, antes da instalação e mais cinco anos durante o experimento, conforme constatado também por Oliveira et al (2003) para um Latossolo Vermelho.…”
Section: Modificação Nos Atributos Físicos Pelo Cultivounclassified
“…Em preparos com baixo grau de mobilização como o plantio direto, observam-se menor macroporosidade e porosidade total na superfície e maior em subsuperfície, quando comparadas com as do preparo convencional (Oliveira et al, 2003;Bertol et al, 2004;Oliveira et al, 2004). As alterações causadas na porosidade do solo, além de modificar as taxas de trocas gasosas, alteram a disponibilidade de água para as plantas.…”
Section: Introductionunclassified
“…The scheduling of this traffic would contribute to minimize soil compaction, and consequently, the losses of productivity . Thus, it is important to determine the soil bearing capacity as a function of soil moisture, and to quantify the damages caused to soil structure, when applied pressures exceed the soil bearing capacity (Dias Junior & Pierce, 1996;Oliveira et al, 2003;Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%